Pengaruh Motif Rasional dan Motif Emosional terhadap Keputusan Pembelian Produk Fashion Muslim : (Studi Kasus Hijab Paris pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Andi Djemma Palopo) - Wandri M; Nurul Ilmi; Salma Sitammu; Nurjannah Nurjannah; Cici Mahmut (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of rational and emotional motives on purchasing decisions of the Muslim fashion product hijab paris among students of the Faculty of Economics and Business at Universitas Andi Djemma Palopo. The research employed a quantitative approach with data collected through questionnaires distributed to 30 respondents. The data were analyzed using multiple linear regression with the assistance of SPSS. The results indicate that both rational and emotional motives significantly influence purchasing decisions for hijab paris, with emotional motives being the most dominant variable. These findings suggest that hijab marketing strategies should take into account the emotional aspects of consumers, particularly among younger generations.